(untitled) (Applied Biological Research, 2018)
The study was aimed to assess the genetic diversity in sandy pear (Pyrus pyrifolia Nakai.) of North-Western Himalayan state of Jammu & Kashmir (India) and to explore and characterize the available genotypes using morphological traits. The genetic variability of 30 sandy pear genotypes collected from the 3 districts of Kashmir were evaluated for various qualitative and quantitative traits. The genotypes showed a considerable genetic diversity and differed significantly for traits like tree, leaf, flower, fruit and yield characters. Fruit weight, fruit firmness, total soluble solids, acidity, juiciness, total sugars, yield and yield efficiency ranged from 21.7-200.4 g, 5.3-9.79 kg cm-2, 9.2-17.0oB, 0.11-0.46%, 32.88-84.05%, 4.50-11.15%, 10.0-805.0 kg tree-1and 0.14-1.72 kg cm-2, respectively, with respective mean values of 68.7±0.78 g, 7.52±0.03 kg cm-2, 12.93±0.08oB, 0.23±0.01%, 64.65 ±0.1%, 7.64±0.06, 177.56±0.46 kg tree-1and 0.57±0.004 kg cm-2. The coefficient of variation was highest for fruit diameter (15.58%), followed by fruit length (10.87%) and lowest for juice content (0.28%), followed by yield (0.45%). Fruit diameter showed a significant positive correlation with fruit length and fruit weight butnegative correlation of fruit diameter was observed with TSS, acidity and sugars. Yield of sandy pear genotypes had positive correlation with yield efficiency.